ESTUDIOS SOBRE EL FLUTTER Y LA FIBRILLATION - ROSENBLUETH, ARTURO; RAMOS GARCIA, J (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1947)
Acetylcholine was applied in varying concns to isolated frog, and turtle hearts The refractory period was always slightly decreased Excitability also was lessened This study proves that shortening of the refractory period is not always accompanied by
ARCH INST CARDIOL MEX
Keywords: ESTUDIOS, FLUTTER, FIBRILLATION; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA